SiRNA/DOX lodeded chitosan based nanoparticles: Development, Characterization and in vitro evaluation on A549 lung cancer cell line - Seifi-Najmi, M; Hajivalili, M; Safaralizadeh, R; Sadreddini, S; Esmaeili, S; Razavi, R; Ahmadi, M; Mikaeili, H; Baradaran, B; Shams-Asenjan, K; Yousefi, M (Cellular and Molecular Biology, 2016)
High-mobility group AT-hook2 (HMGA2), involved in epithelial mesenchymal transition (EMT) process, has a pivotal role in lung cancer metastasis. Lung cancer therapy with HMGA2 suppressing small interfering RNA (siRNA) has been introduced recently while doxorubicin (DOX) has been used as a frequent cancer chemotherapy agent. Both reagents have been faced with obstacles in clinic which make them ineffective. NanoParticles (NPs) provided a platform for efficient co delivery of the anticancer drugs. The aim of this study was production and in vitro characterization of different pharmacological groups (siRNA, DOX or siRNA-DOX) of carboxymethyl dextran thrimethyl chitosan nanoparticles (CMDTMChiNPs) on cytotoxicity, gene expression, apoptosis and migration of metastatic lung cancer cell line (A-549). CMDTMChiNPs were synthesized and encapsulated with siRNA, DOX or siRNA-DOX. Then the effects of HMGA2 siRNA and DOX co delivery was assessed in A549 viability and target genes (HMGA2, Ecadherin, vimentin and MMP9) by MTT and real time PCR, respectively. In addition capability of apoptosis induction and anti-migratory features of formulated NPs were analyzed by flowcytometry and wound healing assays. SiRNA-DOX-CMDTM ChiNPs approximate size were 207±5 with poly dispersity index (PDI) and zeta potential of 0.4 and 16.3±0.3, respectively. NPs loaded with DOX and siRNA were the most efficient drug formulations in A549 cell cytotoxicity, altering of EMT markers, apoptosis induction and migration inhibition. Generally our results showed that co delivery of HMGA2 siRNA and DOX by novel designed CMDTMChiNPs is a new therapeutic approach with great potential efficiency for lung cancer treatment.